Bibliometric Analysis of the Role of Nurses in Addressing Urban and Rural Public Health Disparities - Rani Eka Arini; Sulistyo Andarmoyo; Muhammad Ammar Muhtadi (Westscience Press, 2024)
This bibliometric analysis study explores the thematic and collaborative dynamics within the field of public health research, particularly focusing on the period from 2000 to 2024. Utilizing VOSviewer, we analyzed keyword occurrences and authorship data to identify central themes and the interconnections between researchers. The analysis reveals a strong emphasis on health disparities, with specific attention to access, quality, and policy issues. The emergence of COVID-19 as a significant research theme highlights the field's responsiveness to global health crises and its impact on existing inequalities. The study also maps out key contributors and their collaboration patterns, providing insights into the intellectual structure and potential gaps in the research community. Our findings emphasize the need for interdisciplinary approaches and greater collaboration to address the multifaceted challenges of global health disparities effectively.